Gender and the pandemic in political ideology: The case of Spain - Izaskun Zuazu (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
Gender gaps in political ideology transformed from traditional gaps (women showing more right-leaning than men) to modern gaps (women showing more left-leaning) in the last four decades in Western countries. However, Spain lagged behind in this transformation. This paper analyses how labour market status and the pandemic can affect gender differences in left-right self-placement using data on 600,000 individuals during 2008-2021. Using various indicators of the incidence of COVID-19, the paper associates the pandemic with an increasing rightwing leaning for both women and men. However, this correlation is stronger for men. While the pandemic made men more moderate and less leftist, it made women less moderate. The estimates crucially account for labour market status and generational replacement: the results show greater polarization among younger generations. The results point to gender as a relevant political cleavage in Spain in the near future.
Keywords: D72; J16; 330; political ideology; COVID-19 pandemic; gender-generational gap; labour market status